The Influence of Dynamic Capabilities on PT Sicha Jaya Sentosa’s Performance - Zahra, Zakiyah Az (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The objective of this research is to examine the influence of dynamic capabilities’ components, which are adaptive capability, abdorptive capability, and innovative capability, on the performance of PT Sicha Jaya Sentosa. This explanatory research explains causal relationship between the variables through hypothesis testing. Using total sampling technique, 105 people are selected as the respondents. The data are analyzed through validity and reliability tests. The hypotheses are assessed through multiple regression analysis using t test, so classical assumption test is also performed. The result of this research indicate that there is a positive and significant influence of adaptive capability and innovative capability on the performance of PT Sicha Jaya Sentosa. Absorptive capability also has a significant influence on the firm performance.Keywords: Dynamic Capabilities, Firm Performance.